Efektivitas Teknik Reinforcement Negatif Dalam Mengurangi Perilaku Agresif Motorik Pada Anak Dengan Gangguan Emosional Dan Perilaku - Gusria Herlina; Marlina Marlina; Rahmahtrisilvia Rahmahtrisilvia; Safaruddin Safaruddin; Endang Sri Handayani (Lembaga Riset dan Inovasi Almatani, 2026)
This study was conducted to address aggressive motor behavior in the form of hitting exhibited by a ninth-grade student with emotional and behavioral disorders (EBD) at Aisyiyah Sijunjung. The behavior occurred spontaneously, repeatedly, and frequently during learning activities, disrupting the learning process and social interactions. The purpose of this study was to examine the effectiveness of negative reinforcement techniques in reducing the frequency of aggressive motor behavior. The research subject consisted of students with EBD, with one student selected as the subject using purposive sampling. The study employed a single subject research (SSR) method with an A-B-A design. Data were collected through direct observation using frequency recording and supported documentation. Data analysis was carried out using visual graphical analysis, focusing on changes in trend direction, level, variability, and overlap between phases. The findings indicated that the frequency of hitting behavior decreased from an average of 7.25 times per session during the initial baseline phase (A1) to 3.67 times during the intervention phase (B), and further declined to 1.8 times during the final baseline phase (A2), with a 0% overlap. The results conclude that negative reinforcement techniques are effective in reducing aggressive motor behavior in students with emotional and behavioral disorders.